Many-Valued logics and translations - D'Ottaviano, Ítala M. Loffredo [UNESP] (1999)
This work presents the concepts of translation and conservative translation between logics. By using algebraic semantics we introduce several conservative translations involving the classical propositional calculus and the many-valued calculi of Post and Lukasiewicz.